Figurative Language Analysis in Song Lyrics 'cindy lou who' by Sabrina Carpenter - Nurfitri, Yusthalya; Otong Setiawan Djauhari (INDO PUBLISHING, 2025)
This study aims to analyze figurative language as used in the lyrics of ‘cindy lou who’ by Sabrina Carpenter. It was selected because it uses a lot of figurative language to convey expressions making the lyrics even more feeling and full of unsaid meaning in it. This study uses a descriptive qualitative approach where the method is content analysing, and the aim is to figure out the nature of figurative language employed and the meaning behind them within the context of the whole song. The variable used to gather the information was the content of the presented lyrics, which was analysed thematically under applicable theories of figurative language. The results indicate that a lot of figurative language such as metaphor, irony, imagery, symbolism and also hyperbole dominates the lyrics of ‘cindy lou who’ are used to enhance the overall poetic style and to translate a sense of emotions and feelings of loss, regret and or longing. Through analysing the instances of these figures of speech, the study also attempts to reveal the implicit messages which are not explicitly expressed by Sabrina Carpenter and to prove how figurative language may influence emotional aspects and aesthetic norms of a musical work itself.